Efforts to Promote Surakarta and Makassar as Children Friendly Towns - Hamudy, Moh Ilham A. (Komunitas, 2015)
This study is about child-friendly city (KLA). This research is motivated by the lack of attention of the local government in protecting children and the issuance of Law No. 35 of 2014 on Protection of Children, which mandates local government obligations in the care of the child. This study sought to describe the various efforts made by the government of Surakarta and Makassar in realizing the KLA, the following supporting factors and obstacles surrounding the KLA embodiment. By using descriptive method and combine it with a qualitative approach, this study found some important points about the efforts of local governments in realizing the KLA. In Surakarta, for example, there have been several child-friendly community health centers (puskesmas). The Puskesmas is equipped with a private lounge complete with a children’s playground. In addition, services for children such as nutrition garden, corner of breast milk, pediatrician, child counseling services and a child abuse victim services also continue to be equipped, and many other programs. No wonder the Ministry of Women Empowerment and Child Protection Republic of Indonesia assessment scoring 713 from a total value of 31 indicators contained in the KLA who had filled the city of Surakarta. Meanwhile, Makassar City has not done a lot of local government programs, because the relatively new Makassar proclaimed KLA and is still central to reform. Among the new programs are being implemented and the Government of Makassar is giving birth certificate free of charge, to build flats in slums, and make the two villages as a pilot project KLA. The factors that affect the embodiment of the KLA it is a commitment. Not only the commitment of the head region, but also all relevant parties. As a cross cutting issue, the KLA also requires institutional capacity. Not only is the capacity of Women Empowerment and Child Protection Agency as a leading sector in the KLA, but also all work units other related areas. The success of the KLA in a city / county is also very dependent on the commitment of all parties concerned built. In addition, the program can not be done KLA in a short time, and require no small cost. Penelitian ini adalah tentang kota layak anak (KLA). Penelitian ini dilatarbelakangi oleh kurangnya perhatian pemerintah daerah dalam melindungi anak dan keluarnya UU No 35 Tahun 2014 tentang Perlindungan Anak yang mengamanatkan kewajiban pemerintah daerah dalam mengurus anak. Penelitian ini berusaha menggambarkan pelbagai upaya yang dilakukan pemerintah Kota Surakarta dan Makassar dalam mewujudkan KLA, berikut faktor pendukung dan penghambat yang melingkupi perwujudan KLA tersebut. Dengan menggunakan metode deskriptif dan memadunya dengan pendekatan kualitatif, penelitian ini menemukan beberapa poin penting tentang upaya pemerintah daerah dalam mewujudkan KLA. Di Surakarta, misalnya, sudah ada beberapa puskesmas ramah anak. Puskemas itu dilengkapi dengan ruang tunggu khusus anak lengkap dengan alat bermainnya. Selain itu, layanan-layanan untuk anak seperti taman gizi, pojok ASI, dokter spesialis anak, layanan konseling anak dan tempat pelayanan korban kekerasan terhadap anak juga terus dilengkapi, dan masih banyak program lainnya. Tidak heran kalau penilaian Kementerian PPPA memberikan skor 713 dari total nilai yang terdapat dalam 31 indikator KLA yang sudah dipenuhi Kota Surakarta. Sedangkan, Kota Makassar belum banyak program yang dikerjakan pemerintah daerah. Pasalnya, Makassar relatif baru mencanangkan KLA dan kini masih tengah melakukan pembenahan. Di antara program yang baru dan sedang dilaksanakan Pemerintah Kota Makassar adalah pemberian akta kelahiran secara gratis, membangun rumah susun di kawasan kumuh, dan menjadikan dua kelurahan sebagai proyek percontohan KLA. Adapun faktor yang memengaruhi perwujudan KLA itu adalah komitmen. Tidak hanya komitmen kepala daerah, tetapi juga semua pihak terkait. Sebagai sebuah isu yang melibatkan pelbagai pihak, KLA juga membutuhkan kapasitas kelembagaan. Tidak hanya kapasitas Badan Pemberdayaan Perempuan dan Perlindungan Anak sebagai leading sector KLA, tetapi semua satuan kerja perangkat daerah terkait lainnya. Selain itu, program KLA tidak bisa dilakukan dalam waktu singkat, dan memerlukan biaya yang tidak sedikit.